Estrés laboral y su incidencia en el desempeño de un docente de la Unidad Educativa Basica Jaime Roldos Aguilera - Santillán Tomalá, Nathaly Esperanza (2021)
This case study was developed in order to determine the incidence of work stress in the teaching performance of the educational unit "Jaime Roldós Aguilera" since this teacher has been affected in a certain way by changes in work modality as a result of of the covid pandemic. Likewise, work stress is exhibited by excessive pressure that has been presented in the work environment and directly affected their performance as a teacher in the educational unit, so this research will be directed to provide an explanation of the situation for which it comes going through and likewise a solution to this problem to improve their working life style. Within this research, a qualitative methodology was used for the analysis and description of the problem, also accompanied by instruments and techniques for psychological and diagnostic application such as the psychological clinical interview, the medical history and the application of psychometric tests. In order to provide the patient with an acute stress reaction psychodiagnosis, all areas where work stress has had repercussions, such as their cognitions, somatic symptoms that the patient presented as well as the deterioration of family and work relationships, had to be evaluated. which also helped to provide him with a therapeutic program to contribute to his improvement in the teacher's life.